1993
DOI: 10.1002/jemt.1070260512
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury during bacterial or fungal sepsis

Abstract: We compared physiological and ultrastructural indices of acute lung injury (ALI) during septic shock caused by taxonomically diverse pathogens to distinguish ALI due to endogenous inflammatory mediators vs. microbial exotoxins or other factors. Conscious rats were infected i.v. with gram-negative Escherichia coli (EC, serotype 055:B5), exotoxin-C producing gram-positive Staphylococcus aureus (SA), or yeast-phase Candida albicans (CA, a clinical isolate). Viable inocula of 10(10) EC, 10(10) SA, or 10(9) CA caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The present study demonstrated that inhalation of ONO-1714 reduced the tissue injury caused by peroxynitrite and suppressed the production of iNOS locally in the lung. Our results for the W/D ratio conflict with the finding of Okamoto et al (37) was injected into mice intravenously (1,26,32). Our results agree with those of a study by Kristof et al (23), using mice lacking the iNOS gene.…”
Section: Rt-pcr For Inossupporting
confidence: 71%
“…The present study demonstrated that inhalation of ONO-1714 reduced the tissue injury caused by peroxynitrite and suppressed the production of iNOS locally in the lung. Our results for the W/D ratio conflict with the finding of Okamoto et al (37) was injected into mice intravenously (1,26,32). Our results agree with those of a study by Kristof et al (23), using mice lacking the iNOS gene.…”
Section: Rt-pcr For Inossupporting
confidence: 71%
“…2 The general scheme of the inflammatory response is outlined in Figure 1. The inflammatory pathways in this particular model are very similar to events related to lung injury caused by ischemia, 3 by the presence of bacteria, 4 or by bacterial lipopolysaccharide. 5 These events trigger complement activation as well as activation of tissue macrophages.…”
Section: The Inflammatory Cascade and Neutrophil Recruitmentmentioning
confidence: 91%
“…Oxygen concentrations at sites of human fungal infection have not been measured directly in vivo, though hypoxemia is often described as part of the clinical picture associated with these infections, even in the lung, that may require invasive or noninvasive oxygen therapy (13,14,53,64,70,98). In addition, CO 2 production is directly coupled to oxygen consumption of eukaryotic cells and sites of hypoxia in vivo often contain increased levels of this gas, whose sensing has been linked to fungal virulence (31,67).…”
Section: What Is Hypoxia and Does It Occur During Human Fungal Pathomentioning
confidence: 99%